2018
DOI: 10.1101/461632
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prenatal exposure to particulate matter (PM2.5) and low birth weight in a Sri Lankan birth cohort

Abstract: Background.About 74% of the Sri Lankan population use biomass in the form of unprocessed wood as the primary cooking fuel. A growing body of evidence from meta-analyses and individual studies although limited by few prospective studies, report that prenatal exposure to particulate matter of size 2.5 µm (PM2.5) emissions from biomass fuel burning may be associated with low birth weight (LBW) (<2500 grams). We present results examining the association between PM2.5 and LBW in context of a birth cohort study in S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 31 publications
(41 reference statements)
1
10
0
Order By: Relevance
“…Associations between socio-demographic factors and exposure to biomass fuel was studied and it was found that women who were aged above 45 years, those with low literacy levels (0-5 years of schooling), engaged in unskilled occupations or homemakers and those from low socio-economic status were significantly associated with biomass fuel use in their lifetime. An increasing trend of using firewood was observed with increasing age in Malawi, which ranged from 33% among women of the age 17-24 years, approximately 45% among 46-55 years to 56.3% between 66-85 years (p< 0.001) [8]. A study in Sri Lanka reported that having less than 10 years of schooling (p<0.05) as well as lower family income (p<0.05) were associated with biomass fuel use which is in line with our observations (p< 0.001) [9].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Associations between socio-demographic factors and exposure to biomass fuel was studied and it was found that women who were aged above 45 years, those with low literacy levels (0-5 years of schooling), engaged in unskilled occupations or homemakers and those from low socio-economic status were significantly associated with biomass fuel use in their lifetime. An increasing trend of using firewood was observed with increasing age in Malawi, which ranged from 33% among women of the age 17-24 years, approximately 45% among 46-55 years to 56.3% between 66-85 years (p< 0.001) [8]. A study in Sri Lanka reported that having less than 10 years of schooling (p<0.05) as well as lower family income (p<0.05) were associated with biomass fuel use which is in line with our observations (p< 0.001) [9].…”
Section: Discussionmentioning
confidence: 94%
“…World Health Organization (WHO) estimates that about 3 billion people use open fire or traditional stoves that are fuelled by kerosene and solid fuels, globally [6]. People from low socio-economic background are forced to use solid fuels as these are available easily in rural areas at a lower cost [7,8]. According to the Tracking SDG7: The Energy Progress Report 2018, if the current pattern continues, 2.3 billion people would be still using biomass in 2030 globally [9].…”
Section: Introductionmentioning
confidence: 99%
“…Models were adjusted for confounders and clustered with respect to household to account for mothers with multiple children aged 5 or under. The most relevant confounders to the Sri Lankan context were identified using a directed acyclic graph (DAG) (Supplementary Figure S1) and are supported by the current literature [2,8,9,20,24]. These were household monthly income, education, area, the use of incense, the use of a vaporiser for mosquitos, and exposure to second-hand tobacco smoke.…”
Section: Discussionmentioning
confidence: 54%
“…Comparable trends are also evident in various Indian studies [13,14] and in a meta-analysis of 19 studies, in which the use of solid fuel was associated with a 35% (95% CI: 23, 48) increased risk of LBW in LMICs [11]. In a study in Sri Lanka's Western Province, a 10-fold increase in household PM 2.5 was associated with a 54% (aOR: 1.54, 95% CI: 1.12, 2.12) increased risk of LBW [9].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation